DEKADENSI MORAL REMAJA (UPAYA PEMBINAAN MORAL OLEH KELUARGA DAN SEKOLAH) - Lasmida Listari (Jurnal Pendidikan Sosiologi dan Humaniora, 2021)
Developments that occur in various fields of life such as information and communication technology, analysis of various social media that attract teenagers to see and apply them. However, the influence of technological advances in addition to having a positive impact also has a negative impact on adolescent morale. There is a moral decline in adolescents, such as being involved in drug use, fighting, fraud, theft, free sex, intolerance, and so on. This is very concerning because adolescents are the next generation of the nation's struggle. This phenomenon is quite unsettling for the community and must receive attention and cooperation from parents and schools as well as the community. The purpose of this paper is to determine the efforts to develop values/morals in adolescents through the family as the smallest unit in society in socializing the values and norms that apply in society. A harmonious family, mutual respect, openness, positive communication, and there is love, so the socialization process of values and norms will be conveyed to children/adolescents well. In addition, efforts to foster moral values in children are carried out at school. Schools are conducive, there is mutual respect, so the transinformation of moral values can be accepted by students well. This effort is made to prevent the decline of adolescent morale so that youthful behavior is morally noble and beneficial to social life.